A sintered composite main phase permanent magnet and its preparation method
By optimizing the components of R-Fe-B and HR-Fe-B alloys, using R2Fe14B and HR2Fe14B compound grains, and introducing heavy rare earth HR elements on the surface of R-Fe-B powder, the problem of unstable magnetic performance of sintered R-Fe-B rare earth permanent magnets in high temperature environments is solved, and the preparation of sintered R-Fe-B and HR-Fe-B composite main phase permanent magnets with low cost, high residual magnetic Br and high coercive Hcj is achieved.
Patent Information
- Application Number
- CN202111471519.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-12-06
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2041-12-06
AI Technical Summary
The existing sintered R-Fe-B rare earth permanent magnets cannot maintain the thermal stability of high residual magnetic Br and magnetic properties under high temperature environments, and the diffusion depth of heavy rare earth HR elements is limited, resulting in inconsistent magnetic properties distribution.
By optimizing the composition of R-Fe-B and HR-Fe-B alloys, R2Fe14B and HR2Fe14B compound grains are used as the main phase, and heavy rare earth HR elements are introduced as diffusion source on the surface of R-Fe-B powder particles, combined with the component optimization design of rare earth-rich grain boundary phases, high coercive force Hcj and inhibition of residual magnetic Br reduction.
A sintered R-Fe-B and HR-Fe-B composite main phase permanent magnet with low cost, high residual magnetic Br and high coercive Hcj is obtained, and has excellent magnetic properties and thermal stability.
Smart Images

Figure BDA0003392688480000121 
Figure BDA0003392688480000151
Abstract
Description
Technical Field
[0001] The invention relates to a sintered composite main-phase permanent magnet and a preparation method thereof, in particular to a sintered R-Fe-B, HR-Fe-B composite main-phase permanent magnet and a preparation method thereof. Background Art
[0002] Nd2Fe 14 Since the sintered Nd-Fe-B rare earth permanent magnet with B compound as the main phase was discovered in 1984, it has been widely used in various motors such as electric vehicle motors, industrial motors, and air conditioning compressors due to its excellent magnetic properties (high saturation magnetization and high magnetic energy product) and is the highest performance permanent magnet among permanent magnets. Since these motors have high operating temperatures, in order to operate normally in high temperature environments, permanent magnets are required to have high remanence Br and coercive force Hcj in high temperature environments.
[0003] In recent years, the grain boundary diffusion method has been used to improve the coercivity Hcj of sintered R-Fe-B rare earth permanent magnets: the heavy rare earth HR is diffused from the surface of the sintered R-Fe-B rare earth permanent magnet to the inside, so that the edge of the main phase grain forms a core-shell structure, obtains high coercivity Hcj and inhibits the reduction of remanence Br. However, during the diffusion process, due to the size of the block sintered R-Fe-B rare earth permanent magnet, the diffusion depth of the heavy rare earth HR element and its low melting point alloy and other low melting point alloys in the sintered R-Fe-B rare earth permanent magnet is very limited and the magnetic property distribution inside the block sintered R-Fe-B rare earth permanent magnet is inconsistent. In order to overcome the shortcomings of grain boundary diffusion technology, a certain technology is used to make R2Fe 14 B and HR2Fe 14 B-type compound grains are randomly and uniformly distributed as the main phase in the permanent magnet, and heavy rare earth HR elements are introduced as diffusion sources on the surface of R-Fe-B powder particles to cause diffusion of heavy rare earth HR elements on the surface of R-Fe-B powder particles. At the same time, through the optimization design of the composition of the rare earth-rich grain boundary phase, the coercive force Hcj is improved and the reduction of the remanence Br is suppressed, and a sintered R-Fe-B and HR-Fe-B composite main phase permanent magnet with excellent magnetic properties is obtained.
[0004] Although the method of adding heavy rare earth HR to replace Nd or Pr-Nd and the method of diffusing heavy rare earth HR elements are used to improve the coercive force Hcj of sintered R-Fe-B permanent magnets. The coercive force Hcj of the sintered R-Fe-B permanent magnet obtained by adding heavy rare earth HR elements to replace Nd or Pr-Nd elements is significantly improved, but the remanence Br is greatly reduced. The remanence Br of the sintered R-Fe-B permanent magnet obtained by the heavy rare earth HR element diffusion method is reduced to a small extent, and the coercive force Hcj is significantly improved. However, during the diffusion process of the heavy rare earth HR element, due to the size of the block sintered R-Fe-B permanent magnet, its diffusion depth in the sintered R-Fe-B permanent magnet is very limited and the magnetic property distribution inside the block sintered R-Fe-B rare earth permanent magnet is inconsistent. The above sintered R-Fe-B rare earth permanent magnet cannot maintain high remanence Br or the thermal stability of the magnetic properties is poor in a high temperature environment.
[0005] Therefore, the development of R2Fe 14 B and HR2Fe 14 B-type compound grains are randomly and uniformly distributed as the main phase in the permanent magnet, and heavy rare earth HR elements are introduced as diffusion sources on the surface of R-Fe-B powder particles. Diffusion of heavy rare earth HR elements occurs on the surface of R-Fe-B powder particles. At the same time, through the optimization design of the composition of the rare earth-rich grain boundary phase, sintered R-Fe-B and HR-Fe-B composite main phase permanent magnets with high remanence Br and high coercivity Hcj are obtained, which has positive significance. Summary of the invention
[0006] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a sintered composite main phase permanent magnet and a preparation method thereof, which reduces the production cost by optimizing the usage of heavy rare earth HR elements, and has excellent magnetic properties even in high temperature environments, thereby obtaining a low-cost sintered R-Fe-B, HR-Fe-B composite main phase high-temperature resistant permanent magnet with high remanence Br and high coercivity Hcj.
[0007] In order to achieve the above object, the technical solution adopted by the present invention is:
[0008] A sintered composite main phase permanent magnet, the sintered composite main phase permanent magnet comprising R2Fe 14 B and HR2Fe 14 The main phase grains of B-type compounds include R-Fe-B alloy and HR-Fe-B alloy. The chemical formula of R-Fe-B alloy is R in atomic percentage. a1 B b1 T c1 Fe 余量 , the chemical formula of HR-Fe-B alloy is HR in atomic percentage a2 B b2 T c2 Fe余量 ; Among them, 13.50≤a1≤14.50, 5.50≤b1≤6.00, 1.00≤c1≤2.50; 16.00≤a2≤22.00, 4.80≤b2≤5.60, 0.05≤c2≤1.20;
[0009] The rare earth R element is Nd, or Nd and Pr; the heavy rare earth HR element is any one or more of Tb, Gd, Dy, and Ho; the T element is any one or more of Cu, Co, Ga, Ni, Zn, Zr, Ti, Nb, Al, V, Cr, and Mo; in terms of atomic percentage, the specific element type of the T element is represented by n in the chemical formula of the R-Fe-B alloy and the HR-Fe-B alloy, respectively. 1T 、n 2T Indicates the atomic percentage content of each element; the weight ratio of R-Fe-B alloy coarse powder to HR-Fe-B alloy coarse powder in the raw material mixed coarse powder is 1.000~0.750:0~0.250.
[0010] The rare earth R element is Nd; the heavy rare earth HR element is Tb, Gd, and Ho; the T element in the R-Fe-B alloy is any one or more of Cu, Co, Ga, Zn, Zr, Ti, and Nb; the T element in the HR-Fe-B alloy is any one or more of Cu, Ga, Zn, and Zr; and the weight ratio of the R-Fe-B alloy coarse powder to the HR-Fe-B alloy coarse powder in the raw material mixed coarse powder is 0.999-0.775:0.001-0.225.
[0011] The heavy rare earth HR elements are Tb and Gd; the T element in the HR-Fe-B alloy is any one or more of Cu, Ga and Zn; the weight ratio of the R-Fe-B alloy coarse powder to the HR-Fe-B alloy coarse powder in the raw material mixed coarse powder is 0.999-0.800:0.001-0.200.
[0012] The atomic percentages of Cu, Zn and Ga in the T element in the R-Fe-B alloy satisfy n 1Cu +n 1Zn ≥n 1Ga ; The atomic percentages of Cu, Zn, Ga and Zr in the T element of the HR-Fe-B alloy satisfy n 2Ga +n 2Zr ≤n 2Cu +n 2Zn ≤2.0×n 2Ga .
[0013] Said 13.70≤a1≤14.20, 5.65≤b1≤5.90, 1.00≤c1≤2.00.
[0014] Said 16.50≤a2≤20.00, 4.80≤b2≤5.45, 0.10≤c2≤0.80.
[0015] Said 17.50≤a2≤19.50.
[0016] The method for preparing the sintered composite main phase permanent magnet comprises the following steps:
[0017] (1) Melting: Melting the raw material of R-Fe-B alloy to obtain R-Fe-B alloy flakes; Melting the raw material of HR-Fe-B alloy to obtain HR-Fe-B alloy flakes or alloy ingots;
[0018] (2) Crushing: The R-Fe-B alloy flakes and the HR-Fe-B alloy flakes or the HR-Fe-B alloy ingots are hydrogen-crushed to form R-Fe-B alloy coarse powder and HR-Fe-B alloy coarse powder;
[0019] (3) Mixing: mixing the R-Fe-B alloy coarse powder with the HR-Fe-B alloy coarse powder to obtain R-Fe-B and HR-Fe-B alloy mixed coarse powder;
[0020] (4) Powder making: R-Fe-B and HR-Fe-B alloy mixed coarse powder is jet milled to obtain R-Fe-B and HR-Fe-B alloy mixed magnetic powder;
[0021] (5) Pressing: The R-Fe-B and HR-Fe-B alloy mixed magnetic powders are subjected to magnetic field orientation pressing and isostatic pressing to obtain a green body;
[0022] (6) Heat treatment: The green body is subjected to three heat treatments in a vacuum environment to obtain a sintered composite main phase permanent magnet.
[0023] The thickness of the R-Fe-B alloy flakes and the HR-Fe-B alloy flakes after smelting is 0.25-0.55 mm; the thickness of the HR-Fe-B alloy ingot is 0.5-2.50 cm; the particle size D50 of the R-Fe-B and HR-Fe-B alloy mixed magnetic powder is 3.50-4.50 μm, and the ratio of the particle size D90 to the particle size D10 is less than 4.8.
[0024] In the heat treatment, the first vacuum heat treatment temperature is 1045-1150° C., and the treatment time is 2-7 hours; the second vacuum heat treatment temperature is 800-1000° C., and the treatment time is 1-4 hours; the third vacuum heat treatment temperature is 400-650° C., and the treatment time is 2-6 hours.
[0025] Beneficial effects of the present invention:
[0026] The present invention adopts a composite main phase alloy method to prepare sintered R-Fe-B and HR-Fe-B composite main phase permanent magnets with high remanence Br and high coercivity Hcj, which can meet the use conditions under high temperature.
[0027] When the atomic percentage of the rare earth R element in the R-Fe-B alloy is less than 13.50%, a rare earth-rich R phase with a sufficiently low melting point cannot be formed, and thus a sufficiently high coercivity Hcj cannot be obtained, and the diffusion efficiency of the heavy rare earth HR element will also be affected. When it is greater than 14.50%, the main phase ratio is reduced, which limits the inability to obtain a sufficiently high remanence Br. Therefore, the present invention reasonably sets the atomic percentage of the rare earth R element in the R-Fe-B alloy to satisfy 13.50≤a1≤14.50.
[0028] When the atomic percentage of boron B in the R-Fe-B alloy is less than 5.50%, the main phase ratio is reduced, resulting in the loss of remanence Br. When the boron B content is greater than 6.00%, the main phase ratio is high, and it is easy to form high melting point precipitates of boride, and it is not easy to form a continuous grain boundary phase of sufficient width, which is not conducive to the diffusion of heavy rare earth HR and the improvement of coercivity Hcj. Therefore, the present invention reasonably sets the atomic percentage of boron B element in the R-Fe-B alloy to meet 5.50≤b1≤6.00.
[0029] The present invention appropriately adds elements such as Cu, Co, Ga, Zn, Zr, Ti and Nb to the R-Fe-B alloy, which has the effects of increasing the Curie point of the R-Fe-B alloy, improving high temperature resistance, improving grain boundary structure, and increasing coercivity Hcj. The atomic percentages of Cu, Zn and Ga elements satisfy n2 Cu +n2 Zn ≥n1 Ga , which can effectively inhibit the excess Nd6Fe 13 Cu-type compounds, R2Fe 17 The formation of RFe2 phase and R-Cu phase promotes the formation of non-magnetic phases or weak magnetic phases such as R-Ga-Cu, R-Zn, R-Ga-Zn, R-Cu-Zn, R-Fe-Ga-Cu-Zn at the grain boundary, effectively isolating or weakening R2Fe 14 B and / or HR2Fe 14 The magnetic coupling between the B main phases improves the coercivity Hcj of the sintered composite main phase permanent magnet and the diffusion effect of the heavy rare earth HR elements along the grain boundaries.
[0030] When the atomic percentage of rare earth R element in HR-Fe-B alloy is less than 16.00%, it is impossible to form a sufficiently low melting point rich heavy rare earth HR phase, and thus it is impossible to provide enough heavy rare earth HR elements for grain boundary diffusion to obtain a sufficiently high coercivity Hcj, and at the same time, it affects the diffusion efficiency of heavy rare earth HR elements. 14The ratio of the main phase of B is reduced, which limits the acquisition of a sufficiently high coercivity Hcj. At the same time, too much heavy rare earth HR is enriched in the grain boundary phase, resulting in the inability to optimize the utilization of the heavy rare earth HR element, which is easy to cause waste. Therefore, the present invention reasonably sets the atomic percentage of the heavy rare earth HR element in the HR-Fe-B alloy to meet 16.00≤a2≤22.00.
[0031] When the atomic percentage of boron B in HR-Fe-B alloy is less than 4.80%, the HR2Fe 14 The ratio of the main phase B decreases and HR6Fe is formed. 13 Cu or HR6Fe 13 Ga, HR2Fe 17 The magnetic phase is not conducive to obtaining high coercivity Hcj, resulting in the inability to optimize the utilization of heavy rare earth HR elements, which is easy to cause waste. When the boron B content is greater than 5.60%, it is easy to form high melting point precipitates of boride, and HR-Fe-B alloy with excellent magnetic properties cannot be obtained. When the boron B content is appropriate, the Fe element in the HR-Fe-B alloy is consumed as much as possible to form HR2Fe 14 B main phase, not easy to form HR6Fe 13 Cu or HR6Fe 13 Ga, HR2Fe 17 The HR-Fe-B alloy has a sintered HR-Fe-B composite main phase, and the HR-Fe-B alloy has a sintered HR-Fe-B composite main phase, and the HR-Fe-B alloy has a sintered HR-Fe-B composite main phase, and the HR-Fe-B alloy has a sintered HR-Fe-B composite main phase, and the HR-Fe-B alloy has a sintered HR-Fe-B composite main phase, and the HR-Fe-B composite main phase ...
[0032] The present invention adjusts the content of elements such as Cu, Zn, Ga, and Zr in the HR-Fe-B alloy so that the atomic percentages of the elements Cu, Zn, Zr, and Ga satisfy n 2Ga +n 2Zr ≤n 2Cu +n 2Zn ≤2.0×n 2Ga . It can suppress Nd6Fe as much as possible 13 Cu or Nd6Fe 13 Ga-type compounds, HR2Fe 17The formation of phase and HRFe2 phase promotes the formation of non-magnetic phases or weak magnetic phases such as HR-Cu, HR-Ga-Cu, HR-Zn, HR-Ga-Zn, HR-Cu-Zn, HR-Fe-Ga-Cu-Zn in the grain boundaries, improves the diffusion effect of heavy rare earth HR along the grain boundaries in the sintered composite main phase permanent magnet, and obtains high coercive force Hcj. DETAILED DESCRIPTION
[0033] The specific implementation modes of the present invention are further described in detail below in conjunction with the embodiments.
[0034] The "remanent magnetism Br" mentioned in the present invention refers to the value of the magnetic flux density corresponding to the point where the magnetic field intensity is zero on the saturation hysteresis loop, and the unit is Tesla (T) or Gauss (Gs).
[0035] The "coercive force Hcj" mentioned in the present invention refers to the magnetic field intensity that is monotonically reduced to zero and then increased in the opposite direction from the saturation magnetization state of the magnet, so that its magnetic polarization intensity decreases to zero along the hysteresis loop, and the unit is Oersted (Oe) or Ampere-meter (A, m).
[0036] The "squareness" described in the present invention is expressed by Hk / Hcj. The bending point magnetic field Hk is the magnetic field corresponding to J=0.9Br on the demagnetization curve, also known as the knee point coercive force.
[0037] The “heavy rare earth HR elements” mentioned in the present invention include nine elements: yttrium (Y), gadolinium (Gd), terbium (Tb), dysprosium (Dy), holmium (Ho), erbium (Er), thulium (Tm), ytterbium (Yb), and lutetium (Lu).
[0038] The "particle size D50" mentioned in the present invention refers to the equivalent diameter of the largest particle when the cumulative distribution in the particle size distribution curve is 50%, the "particle size D90" refers to the equivalent diameter of the largest particle when the cumulative distribution in the particle size distribution curve is 90%, and the "particle size D10" refers to the equivalent diameter of the largest particle when the cumulative distribution in the particle size distribution curve is 10%.
[0039] The inventors optimize the contents of rare earth R, heavy rare earth HR, B, Co, Ga, Cu, Zr, Nb, Ti, Zn and Fe elements, and further limit the Cu, Ga, Zn and Zr elements in a specific ratio, thereby obtaining sintered R-Fe-B and HR-Fe-B composite main phase permanent magnets with low cost, high remanence Br and high coercivity Hcj. The sintered R-Fe-B and HR-Fe-B composite main phase permanent magnets are analyzed, and it is believed that the Nd6Fe 13 Ga or Nd6Fe 13 Cu-type compounds, R2Fe 17The phase and RFe2 phase have a significant influence on the coercivity Hcj of sintered R-Fe-B and HR-Fe-B composite main phase permanent magnets and the diffusion effect of heavy rare earth HR elements along the grain boundaries.
[0040] It is known that Nd6Fe 13 Ga or Nd6Fe 13 Cu-type compounds, R2Fe 17 Phase and RFe2 phase are formed at the grain boundary, that is, R6Fe 13 Cu、HR6Fe 13 Cu、HR2Fe 17 , R2Fe 17 Compounds such as Nd6Fe and Nd6Fe have ferromagnetism and cannot effectively weaken the magnetic coupling between the main phases, resulting in a sharp decrease in the coercivity Hcj of the sintered R-Fe-B and HR-Fe-B composite main phase permanent magnets. Therefore, it is necessary to adjust the composition of the R-Fe-B and HR-Fe-B alloys and reduce the Nd6Fe 13 Ga or Nd6Fe 13 Cu-type compounds, R2Fe 17 The content of phase and RFe2 phase is controlled within a certain range or the formation is inhibited, and non-magnetic phases or weak magnetic phases such as (R, HR)-Cu, (R, HR)-Ga-Cu, (R, HR)-Zn, (R, HR)-Ga-Zn, (R, HR)-Cu-Zn, (R, HR)-Fe-Ga-Cu-Zn, etc. can be preferentially generated in the grain boundaries of sintered R-Fe-B and HR-Fe-B composite main phase permanent magnets, effectively isolating or weakening R2Fe 14 B and / or HR2Fe 14 The magnetic coupling between the B main phases can ensure the high coercivity Hcj of the sintered R-Fe-B and HR-Fe-B composite main phase permanent magnets and the diffusion effect of heavy rare earth HR elements along the grain boundaries.
[0041] The sintered R-Fe-B and HR-Fe-B composite main phase permanent magnets of the present invention:
[0042] The sintered R-Fe-B and HR-Fe-B composite main phase permanent magnets of the present invention include R2Fe 14 B and HR2Fe 14 The main phase grains of B-type compounds, the chemical formula of R-Fe-B alloy in its raw materials is R in atomic percentage a1 B b1 T c1 Fe 余量 , the chemical formula of HR-Fe-B alloy is HR in atomic percentage a2 B b2 T c2 Fe 余量 .
[0043] The rare earth R element is Nd, or Nd and Pr, preferably Nd;
[0044] The heavy rare earth HR element is any one or more of Tb, Gd, Dy and Ho, preferably Tb, Gd and Ho, more preferably Tb and Gd;
[0045] The T element is any one or more of Cu, Co, Ga, Ni, Zn, Zr, Ti, Nb, Al, V, Cr and Mo. The specific element types of the T element are represented by n in the chemical formula of R-Fe-B alloy and HR-Fe-B alloy, respectively, in terms of atomic percentage. 1T 、n 2T Indicates the atomic percentage of each element;
[0046] The T element in the R-Fe-B alloy is preferably any one or more of Cu, Co, Ga, Zn, Zr, Ti and Nb; the T element in the HR-Fe-B alloy is preferably any one or more of Cu, Ga, Zn and Zr, more preferably any one or more of Cu, Ga and Zn;
[0047] The atomic percentage of the rare earth R element in the R-Fe-B alloy satisfies 13.50≤a1≤14.50, preferably 13.70≤a1≤14.20; the atomic percentage of the B element in the R-Fe-B alloy satisfies 5.50≤b1≤6.00, preferably 5.65≤b1≤5.90; the atomic percentage of the T element in the R-Fe-B alloy satisfies 1.00≤c1≤2.50, preferably 1.00≤c1≤2.00;
[0048] The atomic percentage of heavy rare earth HR element in the HR-Fe-B alloy satisfies 16.00≤a2≤22.00, preferably 16.50≤a2≤20.00, and more preferably 17.50≤a2≤19.50; the atomic percentage of B element in the HR-Fe-B alloy satisfies 4.80≤b2≤5.60, preferably 4.80≤b2≤5.45; the atomic percentage of T element in the HR-Fe-B alloy satisfies 0.05≤c2≤1.20, preferably 0.10≤c2≤0.80.
[0049] The atomic percentage of the rare earth R element in the R-Fe-B alloy satisfies 13.50≤a1≤14.50, preferably 13.70≤a1≤14.20. When the rare earth R element (a1) is less than 13.50%, it is impossible to form a rare earth-rich R phase with a sufficiently low melting point, and thus it is impossible to obtain a sufficiently high coercivity Hcj, and it will also affect the diffusion efficiency of the heavy rare earth HR element. When it is greater than 14.50%, the main phase ratio is reduced, which limits the inability to obtain a sufficiently high remanence Br.
[0050] Atomic percentage of boron B element in R-Fe-B alloy The atomic percentage of B element in R-Fe-B alloy satisfies 5.50≤b1≤6.00, preferably 5.65≤b1≤5.90. When the boron B content (b1) is less than 5.50%, the main phase ratio is reduced, resulting in remanence Br loss. When the boron B content (b1) is greater than 6.00%, the main phase ratio is high, and it is easy to form high melting point precipitates of boride, and it is not easy to form a continuous grain boundary phase of sufficient width, which is not conducive to the diffusion of heavy rare earth RH and the increase of coercivity Hcj.
[0051] The atomic percentage of the T element in the R-Fe-B alloy satisfies 1.00≤c1≤2.50, preferably 1.00≤c1≤2.00, and the T element is preferably any one or more of Cu, Co, Ga, Zn, Zr, Ti and Nb. Appropriate addition of elements such as Cu, Co, Ga, Zn, Zr, Ti and Nb has the effects of increasing the Curie point of the R-Fe-B alloy, increasing high temperature resistance, improving grain boundary structure, and increasing coercivity Hcj.
[0052] In addition, the Cu content, Zn content and Ga content in the T element of the R-Fe-B alloy satisfy n 1Cu +n 1Zn ≥n 1Ga , when the copper Cu content (n 1Cu ) and zinc content (n 1Zn ) is less than the gallium Ga content (n 1Ga ) when R-Fe-B alloy may form excessive Nd6Fe 13 Ga-type compounds, R2Fe 17 phase and RFe2 phase, which is not conducive to improving the coercivity Hcj of sintered R-Fe-B and HR-Fe-B composite main phase permanent magnets and the diffusion effect of heavy rare earth HR elements along the grain boundaries. 1Cu ) and zinc content (n 1Zn ) is greater than or equal to the gallium Ga content (n 1Ga ) is to suppress the formation of excessive Nd6Fe in the R-Fe-B alloy as much as possible. 13 Cu-type compounds, R2Fe 17 phase and RFe2 phase, and promote the priority formation of non-magnetic phases or weak magnetic phases such as R-Cu, R-Ga-Cu, R-Zn, R-Ga-Zn, R-Cu-Zn, R-Fe-Ga-Cu-Zn in the grain boundaries, effectively isolating or weakening the R2Fe 14 B and or HR2Fe 14 The magnetic coupling between the B main phases improves the coercivity Hcj of the sintered R-Fe-B and HR-Fe-B composite main phase permanent magnets and the diffusion effect of heavy rare earth HR elements along the grain boundaries.
[0053] The atomic percentage of heavy rare earth HR elements in HR-Fe-B alloys satisfies 16.00≤a2≤22.00, preferably 16.50≤a2≤20.00, and more preferably 16.50≤a2≤19.50. When the rare earth R element (a2) is less than 16.00%, it is impossible to form a sufficiently low melting point rich heavy rare earth HR phase, and thus it is impossible to provide enough heavy rare earth HR elements for grain boundary diffusion to obtain a sufficiently high coercivity Hcj, and at the same time, it affects the diffusion efficiency of heavy rare earth HR elements. When it is greater than 22.00%, HR2Fe 14 The B main phase ratio is reduced, which limits the acquisition of a sufficiently high coercivity Hcj. At the same time, too much heavy rare earth HR is enriched in the grain boundary phase, resulting in the failure to optimize the utilization of heavy rare earth HR elements and easily causing waste.
[0054] The atomic percentage of the B element in the HR-Fe-B alloy satisfies 4.80≤b2≤5.60, preferably 4.80≤b2≤5.50. When the boron B content (b2) is less than 4.80%, the HR2Fe in the HR-Fe-B alloy 14 The ratio of the main phase B decreases and HR6Fe is formed. 13 Cu or HR6Fe 13 Ga, HR2Fe 17 The magnetic phase is not conducive to obtaining high coercivity Hcj, resulting in the inability to optimize the utilization of heavy rare earth HR elements, which is easy to cause waste. When the boron B content (b2) is greater than 5.60%, it is easy to form high melting point precipitates of boride, and HR-Fe-B alloy with excellent magnetic properties cannot be obtained. When the boron B content (b2) is appropriate, the Fe element in the HR-Fe-B alloy is consumed as much as possible to form HR2Fe 14 B main phase, not easy to form HR6Fe 13 Cu or HR6Fe 13 Ga, HR2Fe 17 The sintered R-Fe-B and HR-Fe-B composite main phase permanent magnets can improve the diffusion effect of heavy rare earth HR along the grain boundaries and obtain high coercive force Hcj.
[0055] The atomic percentage content of the T element in the HR-Fe-B alloy satisfies 0.05≤c2≤1.20, preferably 0.10≤c2≤0.80, more preferably 0.10≤c2≤0.40, and the T element is preferably at least one of Cu, Ga, Zn and Zr, and the Cu content and the Zn content and the Ga content and the Zr content satisfy n 2Ga +n 2Zr ≤n 2Cu +n 2Zn≤2.0×n 2Ga When the copper content (n 2Cu ) and zinc content (n 2Zn ) is less than the gallium Ga content (n 2Ga ) is 0.5 times, excessive HR6Fe may be formed in the HR-Fe-B alloy 13 Ga-type compounds, HR2Fe 17 phase and HRFe2 phase, which is not conducive to obtaining high coercivity Hcj. 2Cu ) and zinc content (n 2Zn ) is greater than the gallium Ga content (n 2Ga ) and zirconium content (n 2Zr ) and, it is possible that excessive Nd6Fe 13 Cu-type compounds are also not conducive to obtaining high coercivity Hcj. By adjusting the content of copper Cu, zinc Zn, gallium Ga, zirconium Zr and other elements in the HR-Fe-B alloy, the formation of Nd6Fe 13 Cu or Nd6Fe 13 Ga-type compounds, HR2Fe 17 phase and HRFe2 phase, and promote the preferential formation of non-magnetic phases or weak magnetic phases such as HR-Cu, HR-Ga-Cu, HR-Zn, HR-Ga-Zn, HR-Cu-Zn, HR-Fe-Ga-Cu-Zn in the grain boundaries, thereby improving the diffusion effect of heavy rare earth HR along the grain boundaries in the sintered R-Fe-B and HR-Fe-B composite main phase permanent magnets, and obtaining high coercive force Hcj.
[0056] The weight ratio of R-Fe-B alloy powder to HR-Fe-B alloy powder in the R-Fe-B and HR-Fe-B alloy mixed coarse powder of the sintered R-Fe-B and HR-Fe-B composite main phase permanent magnet described in the present invention is 1.000-0.750:0-0.250, preferably 0.999-0.775:0.001-0.225, and more preferably 0.999-0.800:0.001-0.200; if the weight ratio of HR-Fe-B alloy powder in the R-Fe-B and HR-Fe-B alloy mixed powder is too high, although high coercivity Hcj can be obtained, the remanence Br is reduced too much, resulting in the failure to obtain a rare earth permanent magnet with high remanence Br and high coercivity Hcj.
[0057] The manufacturing method of the sintered R-Fe-B and HR-Fe-B composite main phase permanent magnet of the present invention:
[0058] The method for manufacturing a sintered R-Fe-B or HR-Fe-B composite main phase permanent magnet of the present invention comprises the following steps:
[0059] (1) Melting: Melting the raw material of R-Fe-B alloy to obtain R-Fe-B alloy flakes; Melting the raw material of HR-Fe-B alloy to obtain HR-Fe-B alloy flakes or alloy ingots; the thickness of R-Fe-B alloy flakes and HR-Fe-B alloy flakes is 0.25 to 0.55 mm; the thickness of HR-Fe-B alloy ingots is 0.5 to 2.50 cm.
[0060] (2) Crushing: The R-Fe-B alloy flakes and the HR-Fe-B alloy flakes or the HR-Fe-B alloy ingots are hydrogen-crushed to form R-Fe-B alloy coarse powder and HR-Fe-B alloy coarse powder;
[0061] (3) Mixing: mixing the R-Fe-B alloy coarse powder and the HR-Fe-B alloy coarse powder according to a weight ratio to obtain R-Fe-B and HR-Fe-B alloy mixed coarse powder;
[0062] (4) Powder preparation: The R-Fe-B and HR-Fe-B alloy mixed coarse powder is subjected to air flow milling to obtain R-Fe-B and HR-Fe-B alloy mixed magnetic powder, the particle size D50 of the magnetic powder is 3.50-4.50 μm, and the ratio of the particle size D90 to the particle size D10 is less than 4.8;
[0063] (5) Pressing: The R-Fe-B and HR-Fe-B alloy mixed magnetic powders are subjected to magnetic field orientation pressing and isostatic pressing to obtain a green body;
[0064] (6) Heat treatment: The green body is subjected to three heat treatments in a vacuum environment to obtain sintered R-Fe-B and HR-Fe-B composite main phase permanent magnets. In a vacuum environment, the first vacuum heat treatment temperature is 1045-1150°C and the treatment time is 2-7h; the second heat treatment temperature is 800-1000°C and the treatment time is 1-4h; the third heat treatment temperature is 400-650°C and the treatment time is 2-6h. The vacuum degree of the vacuum environment is required to be less than 5×10 -2 Pa.
[0065] The sintered R-Fe-B and HR-Fe-B composite main phase permanent magnets of the present invention have both high remanence Br and high coercivity Hcj, and have excellent magnetic properties even in a high temperature environment. The utilization of the heavy rare earth HR element is optimized, the production cost is reduced, and a sintered R-Fe-B and HR-Fe-B composite main phase permanent magnet with low cost, high remanence Br and high coercivity Hcj is obtained.
[0066] Examples 1 to 18
[0067] The chemical formula of the R-Fe-B alloy in the sintered R-Fe-B and HR-Fe-B composite main phase permanent magnets of Examples 1 to 18 of the present invention is Nd 13.90 B 5.75 Co 1.00 Cu 0.30 Ga 0.20 Zn 0.10 Zr 0.05 Ti 0.10 Fe 余量 , and satisfy n 2Cu +n 2Zn ≥n 1Ga ; The chemical formula of HR-Fe-B alloy is Tb in atomic percentage 18.50 B 5.35 Cu 0.20 Ga 0.20 Zn 0.20 Fe 余量 , and satisfy n 2Ga +n 2Zr ≤n 2Cu +n 2Zn ≤2.0×n 2Ga ;
[0068] The sintered Nd-Fe-B and Tb-Fe-B composite main phase permanent magnets are made by the following steps:
[0069] Melting: After melting the raw materials of Nd-Fe-B alloy, Nd-Fe-B alloy flakes with an average thickness of 0.358 mm are obtained; after melting the raw materials of Tb-Fe-B alloy, Tb-Fe-B alloy flakes with an average thickness of 0.347 mm are obtained;
[0070] Crushing: The Nd-Fe-B alloy flakes and the Tb-Fe-B alloy flakes are hydrogen-crushed to form coarse powders;
[0071] Mixing: The Nd-Fe-B alloy coarse powder and the Tb-Fe-B alloy coarse powder are mixed according to a weight ratio to obtain Nd-Fe-B and Tb-Fe-B alloy mixed coarse powders, that is, the weight ratios of Nd-Fe-B alloy powder and Tb-Fe-B alloy powder in the Nd-Fe-B and Tb-Fe-B alloy mixed coarse powders in Examples 1 to 18 are 0.990:0.010, 0.980:0.020, 0.970:0.030, 0.960:0.040, and 0.980:0.050, respectively. 0.950: 0.050、0.940: 0.060、0.930: 0.070、0.920: 0.080、0.910: 0.090、0.900: 0.100、0.890: 0.110、0.880: 0.120、0.870: 0.130、0.860: 0.140、0.850: 0.150、0.840: 0.160、0.830: 0.170、0.820: 0.180;
[0072] Powder preparation: The Nd-Fe-B and Tb-Fe-B alloy mixed coarse powders were jet milled to obtain Nd-Fe-B and Tb-Fe-B alloy magnetic powders. The particle sizes D50 of the magnetic powders in Examples 1 to 18 were 4.22 μm, 4.17 μm, 4.24 μm, 4.28 μm, 4.24 μm, 4.18 μm, 4.23 μm, 4.15 μm, 4.21 μm, 4.22 μm, 4.24 μm, 4.28 μm, 4.22μm, 4.26μm, 4.22μm, 4.25μm, 4.27μm, 4.22μm, and the ratios of particle size D90 to particle size D10 are 4.52, 4.48, 4.59, 4.62, 4.55, 4.57, 4.46, 4.52, 4.57, 4.60, 4.53, 4.46, 4.49, 4.61, 4.51, 4.52, 4.53, 4.51;
[0073] Pressing: Nd-Fe-B and Tb-Fe-B alloy magnetic powders are pressed by magnetic field orientation and isostatic pressing to obtain green compacts;
[0074] Heat treatment: The green body was heat treated three times in a vacuum environment to obtain sintered Nd-Fe-B and Tb-Fe-B composite main phase permanent magnets. In a vacuum environment, the first vacuum heat treatment temperature was 1075°C and the treatment time was 3.5h; the second heat treatment temperature was 900°C and the treatment time was 2h; the third heat treatment temperature was 485°C and the treatment time was 4h.
[0075] Examples 19 to 24
[0076] The chemical formula of the R-Fe-B alloy in the sintered R-Fe-B and HR-Fe-B composite main phase permanent magnets of Examples 19 to 24 of the present invention is Nd 13.75 B 5.80 Co 1.20 Cu 0.20 Ga 0.10 Zn 0.10 Zr 0.15 Fe 余量 , and satisfy n 2Cu +n 2Zn ≥n 1Ga ; The chemical formula of HR-Fe-B is Tb in atomic percentage 17.50 B 5.45 Cu 0.20 Ga 0.20 Zn 0.10 Zr 0.10 Fe 余量 , and satisfy n 2Ga +n 2Zr ≤n 2Cu +n 2Zn ≤2.0×n 2Ga ;
[0077] The sintered Nd-Fe-B and Tb-Fe-B composite main phase permanent magnets are made by the following steps:
[0078] Smelting: After the raw materials of Nd-Fe-B alloy are smelted, Nd-Fe-B alloy flakes are obtained, with an average thickness of 0.353 mm; after the raw materials of Tb-Fe-B alloy are smelted, Tb-Fe-B alloy ingots are obtained, with an average thickness of 1.95 cm;
[0079] Crushing: Nd-Fe-B alloy flakes and Tb-Fe-B alloy ingots are hydrogen-crushed to form Nd-Fe-B alloy coarse powder and Tb-Fe-B alloy coarse powder respectively;
[0080] Mixing: Nd-Fe-B alloy coarse powder and Tb-Fe-B alloy coarse powder are mixed according to a weight ratio to obtain Nd-Fe-B and Tb-Fe-B alloy mixed coarse powders, that is, the weight ratios of Nd-Fe-B alloy powder and Tb-Fe-B alloy powder in the Nd-Fe-B and Tb-Fe-B alloy mixed coarse powders in Examples 19 to 24 are 0.990:0.010, 0.980:0.020, 0.960:0.040, 0.930:0.070, 0.880:0.120, and 0.820:0.180, respectively;
[0081] Powder preparation: The mixed coarse powder of Nd-Fe-B and Tb-Fe-B alloys was subjected to jet milling to obtain Nd-Fe-B and Tb-Fe-B alloy magnetic powders. The particle size D50 of the magnetic powders in Examples 19 to 24 was 4.27 μm, 4.19 μm, 4.20 μm, 4.21 μm, 4.25 μm, and 4.23 μm, respectively, and the ratios of the particle size D90 to the particle size D10 were 4.55, 4.51, 4.46, 4.53, 4.47, and 4.56, respectively;
[0082] Pressing: the same as the sintered Nd-Fe-B and Tb-Fe-B composite main phase permanent magnets of Examples 1 to 18;
[0083] Heat treatment: the same as that of the sintered Nd-Fe-B and Tb-Fe-B composite main phase permanent magnets of Examples 1 to 18.
[0084] Comparative Example 1
[0085] The weight ratio of Nd-Fe-B alloy powder to Tb-Fe-B alloy powder in the Nd-Fe-B and Tb-Fe-B alloy mixed coarse powder of the sintered Nd-Fe-B and Tb-Fe-B composite main phase permanent magnet of Comparative Example 1 of the present invention is 0.800:0.200; the particle size D50 of the magnetic powder is 4.23 μm, and the ratio of the particle size D90 to the particle size D10 is 4.62. Others are the same as the sintered Nd-Fe-B and Tb-Fe-B composite main phase permanent magnets of Examples 1 to 18.
[0086] Comparative Example 2
[0087] The chemical formula of Nd-Fe-B in the sintered Nd-Fe-B and Tb-Fe-B composite main phase permanent magnets of Comparative Example 2 of the present invention is Nd 13.00 B 5.75 Co 1.00 Cu 0.20 Ga 0.20 Zn 0.10 Ti 0.15 Fe 余量 , satisfying n 1Cu +n 1Zn ≥n 1Ga ; The average thickness of the Nd-Fe-B alloy flakes is 0.357 mm; The weight ratio of the Nd-Fe-B alloy powder to the Tb-Fe-B alloy powder in the Nd-Fe-B and Tb-Fe-B alloy mixed coarse powder is 0.930:0.070; The particle size D50 of the magnetic powder is 4.27 μm, and the ratio of the particle size D90 to the particle size D10 is 4.58. Others are the same as the sintered Nd-Fe-B and Tb-Fe-B composite main phase permanent magnets of Examples 1 to 18.
[0088] Comparative Example 3
[0089] The chemical formula of the Tb-Fe-B alloy in the sintered Nd-Fe-B, Tb-Fe-B composite main phase permanent magnet of Comparative Example 3 of the present invention is Tb 15.00 B 5.65 Cu 0.10 Ga 0.15 Zn 0.10 Zr 0.05 Fe 余量 , satisfying n 2Ga +n 2Zr ≤n 2Cu +n 2Zn ≤2.0×n 2Ga The average thickness of the Tb-Fe-B alloy flakes is 0.346 mm. The weight ratio of the Nd-Fe-B alloy powder to the Tb-Fe-B alloy powder in the Nd-Fe-B and Tb-Fe-B alloy mixed coarse powder is 0.930:0.070. The particle size D50 of the magnetic powder is 4.17 μm, and the ratio of the particle size D90 to the particle size D10 is 4.70. Others are the same as those of the sintered Nd-Fe-B and Tb-Fe-B composite main phase permanent magnets of Examples 1 to 18.
[0090] Comparative Example 4
[0091] The chemical formula of the Tb-Fe-B alloy in the sintered Nd-Fe-B, Tb-Fe-B composite main phase permanent magnet of Comparative Example 4 of the present invention is Tb 17.50 B 4.60 Cu 0.15 Ga 0.15 Zn 0.10 Zr 0.05 Fe 余量 , satisfying n 2Ga +n 2Zr ≤n 2Cu +n 2Zn ≤2.0×n 2Ga ; The average thickness of the Tb-Fe-B alloy flakes is 0.356 mm; The weight ratio of the Nd-Fe-B alloy powder to the Tb-Fe-B alloy powder in the Nd-Fe-B and Tb-Fe-B alloy mixed coarse powder is 0.930:0.070; The particle size D50 of the magnetic powder is 4.27 μm, and the ratio of the particle size D90 to the particle size D10 is 4.65. Others are the same as the sintered Nd-Fe-B and Tb-Fe-B composite main phase permanent magnets of Examples 1 to 18.
[0092] Comparative Example 5
[0093] The chemical formula of the Tb-Fe-B alloy in the sintered Nd-Fe-B, Tb-Fe-B composite main phase permanent magnet of Comparative Example 5 of the present invention is Tb 17.50 B4.90 Cu 0.15 Ga 0.15 Zn 0.08 Zr 0.05 Fe 余量 , satisfying n 2Ga +n 2Zr ≤n 2Cu +n 2Zn ≤2.0×n 2Ga The average thickness of the Tb-Fe-B alloy flakes is 0.353 mm. The weight ratio of the Nd-Fe-B alloy powder to the Tb-Fe-B alloy powder in the Nd-Fe-B and Tb-Fe-B alloy mixed coarse powder is 0.930:0.070. The particle size D50 of the magnetic powder is 4.26 μm, and the ratio of the particle size D90 to the particle size D10 is 4.67. Others are the same as those of the sintered Nd-Fe-B and Tb-Fe-B composite main phase permanent magnets of Examples 1 to 18.
[0094] Comparative Example 6
[0095] The chemical formula of the Tb-Fe-B alloy in the sintered Nd-Fe-B, Tb-Fe-B composite main phase permanent magnet of Comparative Example 6 of the present invention is Tb 17.00 B 5.90 Cu 0.30 Ga 0.10 Zn 0.10 Zr 0.05 Fe 余量 , does not satisfy n 2Ga +n 2Zr ≤n 2Cu +n 2Zn ≤2.0×n 2Ga ; The average thickness of the Tb-Fe-B alloy flakes is 0.359 mm; The weight ratio of Nd-Fe-B alloy powder to Tb-Fe-B alloy powder in the Nd-Fe-B and Tb-Fe-B alloy mixed coarse powder is 0.930:0.070; The particle size D50 of the magnetic powder is 4.23 μm, and the ratio of the particle size D90 to the particle size D10 is 4.61. Others are the same as the sintered Nd-Fe-B and Tb-Fe-B composite main phase permanent magnets of Examples 1 to 18.
[0096] Comparative Example 7
[0097] The chemical formula of the Tb-Fe-B alloy in the sintered Nd-Fe-B, Tb-Fe-B composite main phase permanent magnet of Comparative Example 7 of the present invention is Tb 17.00 B 5.90 Cu 0.10 Ga 0.25 Zn 0.10 Zr 0.05 Fe 余量, does not satisfy n 2Ga +n 2Zr ≤n 2Cu +n 2Zn ≤2.0×n 2Ga The average thickness of the Tb-Fe-B alloy flakes is 0.351 mm. The weight ratio of the Nd-Fe-B alloy powder to the Tb-Fe-B alloy powder in the Nd-Fe-B and Tb-Fe-B alloy mixed coarse powder is 0.930:0.070. The particle size D50 of the magnetic powder is 4.21 μm, and the ratio of the particle size D90 to the particle size D10 is 4.57. Others are the same as those of the sintered Nd-Fe-B and Tb-Fe-B composite main phase permanent magnets of Examples 1 to 18.
[0098] Comparative Example 8
[0099] The chemical formula of the Tb-Fe-B alloy in the sintered Nd-Fe-B, Tb-Fe-B composite main phase permanent magnet of Comparative Example 8 of the present invention is Tb 17.00 B 5.50 Fe 余量 The average thickness of the Tb-Fe-B alloy ingot is 1.82 cm. The weight ratio of the Nd-Fe-B alloy powder to the Tb-Fe-B alloy powder in the Nd-Fe-B and Tb-Fe-B alloy mixed coarse powder is 0.930:0.070. The particle size D50 of the magnetic powder is 4.25 μm, and the ratio of the particle size D90 to the particle size D10 is 4.53. Others are the same as those of the sintered Nd-Fe-B and Tb-Fe-B composite main phase permanent magnets of Examples 19 to 24.
[0100] Comparative Example 9
[0101] The chemical formula of Tb-Fe-B in the sintered Nd-Fe-B, Tb-Fe-B composite main phase permanent magnet of Comparative Example 9 of the present invention is Tb 23.00 B 6.00 Cu 0.20 Ga 0.15 Zn 0.10 Fe 余量 , satisfying n 2Ga +n 2Zr ≤n 2Cu +n 2Zn ≤2.0×n 2Ga ; The average thickness of the Tb-Fe-B alloy flakes is 0.351 mm; The weight ratio of Nd-Fe-B alloy powder to Tb-Fe-B alloy powder in the Nd-Fe-B and Tb-Fe-B alloy mixed coarse powder is 0.930:0.070; The particle size D50 of the magnetic powder is 4.12 μm, and the ratio of the particle size D90 to the particle size D10 is 4.55. Others are the same as the sintered Nd-Fe-B and Tb-Fe-B composite main phase permanent magnets of Examples 1 to 18.
[0102] Table 1
[0103]
[0104] It can be seen from Table 1 that the weight ratio of Nd-Fe-B alloy powder to Tb-Fe-B alloy powder in the Nd-Fe-B and Tb-Fe-B alloy mixed coarse powder, the rare earth Nd content, the heavy rare earth Tb element content, the T element content and type, and the thin sheet or ingot of Tb-Fe-B alloy have an impact on the remanence Br and coercivity Hcj of the sintered Nd-Fe-B and Tb-Fe-B composite main phase permanent magnets.
[0105] Compared with the comparative example 1, as the weight ratio of Nd-Fe-B alloy powder to Tb-Fe-B alloy powder in the mixed coarse powder of Nd-Fe-B and Tb-Fe-B alloy changes, that is, the weight of Tb-Fe-B alloy powder increases, the coercivity Hcj of the sintered Nd-Fe-B and Tb-Fe-B composite main phase permanent magnets gradually increases, and the remanence Br decreases to a small extent. However, when the weight of Tb-Fe-B alloy powder increases to 20%, the coercivity Hcj of the sintered Nd-Fe-B and Tb-Fe-B composite main phase permanent magnets increases to a low extent, and the remanence Br decreases to 11.43 kGs. The main reason is that the Tb2Fe 14 The ratio of the main phase of B is high, and the content of Nd-Fe-B alloy is too little, which limits the improvement of the remanence Br of the permanent magnet. At the same time, the heavy rare earth Tb element cannot be effectively diffused to form a core-shell structure, and is enriched at the grain boundary, which cannot further improve the coercivity Hcj. When the content of Tb-Fe-B alloy powder in the mixed powder is too high, the sintered Nd-Fe-B, Tb-Fe-B composite main phase permanent magnet with high remanence Br and high coercivity Hcj cannot be obtained, and the heavy rare earth Tb element cannot be effectively utilized, resulting in waste.
[0106] Compared with Comparative Example 2, when the rare earth R content in the Nd-Fe-B alloy is reduced to 13.00%, the remanence Br and coercive force Hcj of the sintered Nd-Fe-B and Tb-Fe-B composite main phase permanent magnets are lower in Examples 7 and 22. The main reason is that the Nd-Fe-B alloy contains less rare earth-rich R phase, and the heavy rare earth Tb element in the Tb-Fe-B alloy cannot effectively diffuse along the grain boundaries, and thus cannot form a core-shell structure, resulting in a low coercive force Hcj.
[0107] Compared with Comparative Example 3, when the content of heavy rare earth Tb element in Tb-Fe-B alloy is reduced to 15.00%, the coercive force Hcj of sintered Nd-Fe-B and Tb-Fe-B composite main phase permanent magnets is lower in Examples 7 and 22. The main reason is that the Tb-Fe-B alloy contains less heavy rare earth Tb-rich phase, and the heavy rare earth Tb element in the Tb-Fe-B alloy diffuses less along the grain boundaries, and thus less core-shell structure is formed, resulting in a low increase in the coercive force Hcj.
[0108] Compared with Comparative Example 4, when the Fe content in the Tb-Fe-B alloy cannot be completely formed in Tb2Fe 14 When the main phase is B, the coercivity Hcj of the sintered Nd-Fe-B and Tb-Fe-B composite main phase permanent magnets is low. The main reason is that excessive Tb2Fe 17 phase, TbFe2 phase and Nd6Fe 13 Cu and Nd6Fe 13 Ga-type compounds, etc. These substances are magnetic, have low saturation magnetization Js, and cannot effectively remove Nd2Fe 14 B. Tb2Fe 14 The coupling effect between the B main phase grains leads to low remanence Br and coercivity Hcj of sintered Nd-Fe-B and Tb-Fe-B composite main phase permanent magnets.
[0109] Compared with Comparative Example 5, when the B element content in the Tb-Fe-B alloy cannot be completely formed in Tb2Fe 14 When B is the main phase, the coercive force Hcj of the sintered Nd-Fe-B and Tb-Fe-B composite main phase permanent magnets is relatively low. The main reason is that high melting point precipitates of boride are easily formed, which leads to the low coercive force Hcj of the sintered Nd-Fe-B and Tb-Fe-B composite main phase permanent magnets.
[0110] Compared with Comparative Examples 6, 7, and 8, when the contents of Cu, Zn, Ga, and Zr in the Tb-Fe-B alloy do not meet the requirements of n 2Ga +n 2Zr ≤n 2Cu +n 2Zn ≤2.0×n 2Ga When sintered, the remanence Br and coercivity Hcj of Nd-Fe-B and Tb-Fe-B composite main phase permanent magnets are low. The main reason is that some Nd6Fe 13 Cu and Nd6Fe 13 Ga-type compounds, Tb2Fe 17 phase, TbFe2 phase, etc. These materials are magnetic, with low saturation magnetization intensity Js, and cannot effectively remove Nd2Fe14 B. Tb2Fe 14 The coupling effect between the B main phase grains leads to low remanence Br and coercivity Hcj of sintered Nd-Fe-B and Tb-Fe-B composite main phase permanent magnets.
[0111] Compared with Comparative Example 9, when the content of heavy rare earth HR element in Tb-Fe-B alloy increases to 23, the coercivity Hcj of sintered Nd-Fe-B and Tb-Fe-B composite main phase permanent magnets is equivalent to that of sintered Nd-Fe-B and Tb-Fe-B composite main phase permanent magnets in Examples 5 and 16, and the remanence Br decreases seriously. The main reason is that Tb-Fe-B alloy contains more heavy rare earth Tb phase, which cannot make all heavy rare earth Tb elements diffuse along the grain boundary to form a core-shell structure. At the same time, Nd2Fe 14 B. Tb2Fe 14 The B main phase grain ratio is reduced, resulting in low remanence Br and coercivity Hcj, and it is impossible to obtain sintered Nd-Fe-B and Tb-Fe-B composite main phase permanent magnets with high remanence Br and high coercivity Hcj. The excessive use of heavy rare earth Tb element also causes waste.
[0112] Compared with comparative examples 1 to 9, the remanence Br and coercive force Hcj of the sintered Nd-Fe-B and Tb-Fe-B composite main phase permanent magnets using Tb-Fe-B alloy flakes in Examples 1 to 24 are higher than those of the sintered Nd-Fe-B and Tb-Fe-B composite main phase permanent magnets using Tb-Fe-B alloy ingots. The main reason is that the microstructure of the Tb-Fe-B alloy flakes is better than that of the Tb-Fe-B alloy ingots, and some α-Fe soft magnetic phases may exist in the Tb-Fe-B alloy ingots, which is not conducive to improving the magnetic properties of the permanent magnets.
[0113] The use of the sintered Nd-Fe-B and Tb-Fe-B composite main phase permanent magnets of the present invention is of great significance for reducing the production cost of sintered rare earth permanent magnets with high remanence Br and high coercivity Hcj, especially saving heavy rare earth Tb elements, and improving the thermal stability and cost performance of the sintered Nd-Fe-B and Tb-Fe-B composite main phase permanent magnets.
[0114] Embodiments 25 to 31
[0115] The components of the Nd-Fe-B alloy and Tb-Fe-B alloy in the sintered R-Fe-B and HR-Fe-B composite main phase permanent magnets of Examples 25 to 31 of the present invention are the same as those of the Nd-Fe-B alloy in Examples 1 to 18; the chemical formula of the other group of HR-Fe-B alloys is Gd in atomic percentage. 18.50 B 5.90 Cu 0.15 Ga 0.1 Zn0.10 Fe 余量 , and satisfy n 2Ga +n 2Zr ≤n 2Cu +n 2Zn ≤2.0×n 2Ga ;
[0116] The sintered Nd-Fe-B, Tb-Fe-B, and Gd-Fe-B composite main phase permanent magnets are prepared by the following steps:
[0117] Melting: Nd-Fe-B alloy and Tb-Fe-B alloy flakes are the same as those in Example 1-18; Gd-Fe-B alloy flakes are obtained by melting the raw materials of Gd-Fe-B alloy, and the average thickness is 0.352 mm;
[0118] Crushing: The Nd-Fe-B alloy flakes, the Tb-Fe-B alloy flakes and the Gd-Fe-B alloy flakes are respectively hydrogen-crushed to form Nd-Fe-B alloy coarse powder, Tb-Fe-B alloy coarse powder and Gd-Fe-B alloy coarse powder;
[0119] Mixing: mixing Nd-Fe-B alloy coarse powder, Tb-Fe-B alloy coarse powder and Gd-Fe-B alloy coarse powder in a certain weight ratio to obtain Nd-Fe-B, Tb-Fe-B and Gd-Fe-B alloy mixed coarse powder, that is, the weight ratios of Nd-Fe-B alloy powder, Tb-Fe-B alloy powder and Gd-Fe-B alloy powder are 0.990:0.005:0.005, 0.970:0.024:0.006, 0.950:0.040:0.010, 0.930:0.063:0.007, 0.910:0.072:0.018, 0.850:0.120:0.030 and 0.820:0.144:0.036 respectively;
[0120] Powder preparation: Nd-Fe-B, Tb-Fe-B and Gd-Fe-B alloy mixed coarse powders were jet milled to obtain Nd-Fe-B, Tb-Fe-B and Gd-Fe-B alloy magnetic powders, the particle sizes D50 of the magnetic powders were 4.23μm, 4.25μm, 4.28μm, 4.15μm, 4.29μm, 4.22μm and 4.21μm, respectively, and the ratios of particle size D90 to particle size D10 were 4.50, 4.47, 4.53, 4.60, 4.56, 4.52 and 4.55, respectively;
[0121] Pressing: Nd-Fe-B, Tb-Fe-B, Gd-Fe-B alloy magnetic powders are subjected to magnetic field orientation pressing and isostatic pressing to obtain green compacts;
[0122] Heat treatment: The green body is subjected to three heat treatments in a vacuum environment to obtain sintered Nd-Fe-B, Tb-Fe-B, and Gd-Fe-B composite main phase permanent magnets. The three heat treatment process regimes are the same as those in Example 1-18.
[0123] Comparative Examples 10 to 12
[0124] The weight ratios of Nd-Fe-B, Tb-Fe-B, and Gd-Fe-B alloy powders in the Nd-Fe-B, Tb-Fe-B, and Gd-Fe-B alloy mixed coarse powders of the sintered Nd-Fe-B, Tb-Fe-B, and Gd-Fe-B composite main phase permanent magnets of Comparative Examples 10 to 12 of the present invention are 0.820:0.126:0.054, 0.820:0.090:0.090, and 0.800:0.160:0.040, respectively; the particle size D50 of the magnetic powder is 4.26 μm, 4.29 μm, and 4.22 μm, respectively, and the ratios of particle size D90 to particle size D10 are 4.54, 4.53, and 4.56, respectively. Others are the same as the sintered Nd-Fe-B, Tb-Fe-B, and Gd-Fe-B composite main phase permanent magnets of Examples 25 to 31.
[0125] Table 2
[0126]
[0127] It can be seen from Table 2 that the Nd-Fe-B alloy powder and Gd-Fe-B alloy powder in the mixed coarse powder of Nd-Fe-B, Tb-Fe-B and Gd-Fe-B alloy have an influence on the remanence Br and coercivity Hcj of the sintered Nd-Fe-B, Tb-Fe-B and Gd-Fe-B composite main phase permanent magnets.
[0128] Compared with Comparative Examples 10, 11, and 12, as the weight ratio of the Gd-Fe-B alloy powder in the Nd-Fe-B, Tb-Fe-B, and Gd-Fe-B alloy mixed coarse powder increases or the weight ratio of the Nd-Fe-B alloy powder decreases, the Gd2Fe 14 B and Tb2Fe 14 Although the increase in the content of B main phase grains can significantly improve the thermal stability of sintered Nd-Fe-B, Tb-Fe-B, and Gd-Fe-B composite main phase permanent magnets, their coercive force Hcj and remanence Br are significantly reduced, and sintered rare earth permanent magnets with high remanence Br and high coercive force Hcj cannot be obtained.
[0129] The use of the sintered Nd-Fe-B, Tb-Fe-B, Gd-Fe-B composite main phase permanent magnets of the present invention is of great significance for reducing the production cost of sintered rare earth permanent magnets with high remanence Br and high coercivity Hcj, especially saving the use of heavy rare earth Tb, and improving the thermal stability and cost performance of the sintered Nd-Fe-B, Tb-Fe-B, Gd-Fe-B composite main phase permanent magnets.
Claims
1. A method for preparing a sintered composite main phase permanent magnet, characterized in that: The sintered composite main phase permanent magnet comprises R2Fe 14 B and HR2Fe 14 The main phase grains of B-type compounds include R-Fe-B alloy and HR-Fe-B alloy. The chemical formula of R-Fe-B alloy is R in atomic percentage. a1 B b1 T c1 Fe 余量 , the chemical formula of HR-Fe-B alloy is HR in atomic percentage a2 B b2 T c2 Fe 余量 ; Among them, 13.50≤a1≤14.50, 5.50≤b1≤6.00, 1.00≤c1≤2.50; 16.00≤a2≤22.00, 4.80≤b2≤5.60, 0.05≤c2≤1.20; In terms of atomic percentage, the specific element type of the T element is represented by n in the chemical formula of the R-Fe-B alloy and the HR-Fe-B alloy. 1T 、n 2T Indicates the atomic percentage of each element; The R element is Nd; the T element in the R-Fe-B alloy is any one or more of Cu, Co, Ga, Zn, Zr, Ti and Nb, and must contain Cu, Ga and Zn; the HR element is Tb and / or Gd; the T element in the HR-Fe-B alloy is Cu, Ga, Zn and Zr; The weight ratio of the R-Fe-B alloy coarse powder to the HR-Fe-B alloy coarse powder in the raw material mixed coarse powder is 0.999-0.800:0.001-0.200; the atomic percentages of Cu, Zn and Ga elements in the T element in the R-Fe-B alloy satisfy n 1Cu +n 1Zn ≥n 1Ga ; The atomic percentages of Cu, Zn, Ga and Zr in the T element of the HR-Fe-B alloy satisfy n 2Ga +n 2Zr ≤n 2Cu +n 2Zn ≤2.0×n 2Ga ; The method for preparing the sintered composite main phase permanent magnet comprises the following steps: (1) Melting: Melting the raw material of R-Fe-B alloy to obtain R-Fe-B alloy flakes; Melting the raw material of HR-Fe-B alloy to obtain HR-Fe-B alloy flakes or alloy ingots; The thickness of the R-Fe-B alloy flakes and the HR-Fe-B alloy flakes after smelting is 0.25-0.55 mm; the thickness of the HR-Fe-B alloy ingot is 0.5-2.50 cm; the particle size D50 of the R-Fe-B and HR-Fe-B alloy mixed magnetic powder is 3.50-4.50 μm, and the ratio of the particle size D90 to the particle size D10 is less than 4.8; (2) Crushing: The R-Fe-B alloy flakes and the HR-Fe-B alloy flakes or the HR-Fe-B alloy ingots are hydrogen-crushed to form R-Fe-B alloy coarse powder and HR-Fe-B alloy coarse powder; (3) Mixing: mixing the R-Fe-B alloy coarse powder with the HR-Fe-B alloy coarse powder to obtain R-Fe-B and HR-Fe-B alloy mixed coarse powder; (4) Powder making: R-Fe-B and HR-Fe-B alloy mixed coarse powder is jet milled to obtain R-Fe-B and HR-Fe-B alloy mixed magnetic powder; (5) Pressing: The R-Fe-B and HR-Fe-B alloy mixed magnetic powders are subjected to magnetic field orientation pressing and isostatic pressing to obtain a green body; (6) Heat treatment: The green body is subjected to three heat treatments in a vacuum environment to obtain a sintered composite main phase permanent magnet; In the heat treatment, the first vacuum heat treatment temperature is 1045-1150° C., and the treatment time is 2-7 hours; the second vacuum heat treatment temperature is 800-1000° C., and the treatment time is 1-4 hours; the third vacuum heat treatment temperature is 400-650° C., and the treatment time is 2-6 hours.
2. The method for preparing a sintered composite main phase permanent magnet according to claim 1, characterized in that: R-Fe-B alloy atomic percentage chemical formula R a1 B b1 T c1 Fe 余量 In the above table, 13.70≤a1≤14.20, 5.65≤b1≤5.90, 1.00≤c1≤2.
00.
3. The method for preparing a sintered composite main phase permanent magnet according to claim 2, characterized in that: HR-Fe-B alloy atomic percentage chemical formula HR a2 B b2 T c2 Fe 余量 In the equation, 16.50≤a2≤20.00, 4.80≤b2≤5.45, and 0.10≤c2≤0.
80.
4. The method for preparing a sintered composite main phase permanent magnet according to claim 3, characterized in that: 17.50≤a2≤19.50。
Citation Information
Patent Citations
Method for improving the coercivity of sintered neodymium iron boroncomposite magnets
CN107689279A
Heavy rare earth alloy, neodymium iron boron permanent magnet material, raw material and preparation method
CN111636035A